Aportación económica y personajes que vinculan a León con Hispanoamérica durante el periodo de su independencia - García Gutiérrez, Patrocinio (Estudios humanísticos. Geografía, historia y arte, 1991)
The province of León is linked to the process of independence in Latin America through its monetary contribution to the Cádiz Reinforcement Commission, created to supress the uprisings in the rebelious colonies, through a series of people (of quite different calibre) who held official posts in that continent and in this province, through those who refused to go and quell those colonies and later received a reward for their services in León, and through those who although resident in this provincial capital had been born in Montevideo and therefore had the right to vote for substitute members of the Parliament of that province.